2013
DOI: 10.1186/1472-6963-13-201
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing participation in a vascular disease prevention lifestyle program among participants in a cluster randomized trial

Abstract: BackgroundPrevious research suggests that lifestyle intervention for the prevention of diabetes and cardiovascular disease (CVD) are effective, however little is known about factors affecting participation in such programs. This study aims to explore factors influencing levels of participation in a lifestyle modification program conducted as part of a cluster randomized controlled trial of CVD prevention in primary care.MethodsThis concurrent mixed methods study used data from the intervention arm of a cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…23,26,27 However, researchers argue that understanding reasons for patients choosing to enroll/not enroll and participate in self-management can be determined by exploring patient attitudes and beliefs on factors that affect recruitment and retention. 28,29 Existing research exploring reasons for low enrollment and high attrition in chronic disease self-management programs has primarily focused on quantitative measures 30,31 to draw conclusions based on associations between patients' demographic factors, patient/provider time spent participating in self-management programs, and using patient feedback at follow-up. Verevkina et al 30 found that low baseline self-efficacy to self-manage chronic disease, younger patient age, and weekday program sessions were significantly associated with high patient attrition from chronic disease self-management programs.…”
Section: Introductionmentioning
confidence: 99%
“…23,26,27 However, researchers argue that understanding reasons for patients choosing to enroll/not enroll and participate in self-management can be determined by exploring patient attitudes and beliefs on factors that affect recruitment and retention. 28,29 Existing research exploring reasons for low enrollment and high attrition in chronic disease self-management programs has primarily focused on quantitative measures 30,31 to draw conclusions based on associations between patients' demographic factors, patient/provider time spent participating in self-management programs, and using patient feedback at follow-up. Verevkina et al 30 found that low baseline self-efficacy to self-manage chronic disease, younger patient age, and weekday program sessions were significantly associated with high patient attrition from chronic disease self-management programs.…”
Section: Introductionmentioning
confidence: 99%
“…The redesign incorporated facilitators to enrollment in self-management support programs such as endorsement by health care providers, encouragement, and support by program facilitator to enroll in the program, and information provision on the purpose of the program. [8][9][10][11] As well, the program is available at no cost and is available on-line and at various locations within the region, minimizing some barriers to enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of factors associated with participation in a lifestyle program for the prevention of cardiovascular disease, unemployment status was one factor associated with higher patient enrollment in the program. 9 Information on employment status was not collected for this study. Therefore, nonworking status associated with age cannot be confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations